2001
DOI: 10.1258/0004563011901037
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates: an overview with special reference to alendronate

Abstract: Bisphosphonates, analogues of pyrophosphate, are potent inhibitors of osteoclast-mediated bone resorption. They are used in the treatment of Paget's disease of bone, hypercalcaemia and osteolytic bone disease of malignancy, primary and secondary hyperparathyroidism,and in osteoporosis. Bisphosphonate treatment causes an early reduction in bone resorption followed by a later reduction in bone formation. The early inhibition of bone resorption induces a reduction in serum calcium which leads to increased parathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(86 citation statements)
references
References 95 publications
3
77
0
5
Order By: Relevance
“…The nonamino-containing bisphosphonates are metabolised to non-hydrolyzable analogues of ATP and thus interfere with the cells' ATP-dependent intracellular enzymes. The end result for the mature osteoclasts seem to be impairment of function and apoptosis for both of these mechanisms, as well as a decrease in recruitment [3,20,25]. In addition, there is evidence suggesting that some bisphosphonates also may prevent osteocyte and osteoblast apoptosis [ 171.…”
mentioning
confidence: 99%
“…The nonamino-containing bisphosphonates are metabolised to non-hydrolyzable analogues of ATP and thus interfere with the cells' ATP-dependent intracellular enzymes. The end result for the mature osteoclasts seem to be impairment of function and apoptosis for both of these mechanisms, as well as a decrease in recruitment [3,20,25]. In addition, there is evidence suggesting that some bisphosphonates also may prevent osteocyte and osteoblast apoptosis [ 171.…”
mentioning
confidence: 99%
“…Bisphosphonates, used initially to treat malignancy- associated humoral hypercalcaemia, have shown promise at decreasing cancer-induced skeletal complications. The suggested mechanism of bisphosphonates' action is a direct inhibition of osteoclast and osteoclast precursor cell activation [Hiraga et al, 2001;Vasikaran, 2001;Neville-Webbe et al, 2002]. Recent reports have shown that bisphosphonate treatment can significantly reduce the number of activated osteoclasts and osteolytic destruction of bone [Breuil et al, 1998;Boissier et al, 2000].…”
Section: Therapies For Cancer-induced Bone Painmentioning
confidence: 99%
“…Nos bisfosfonatos, o átomo central de oxigênio do pirofosfato é substituído por um átomo de carbono, ao qual dois radicais fosfato são ligados . Essa estrutura confere aos bisfosfonatos, afinidade por hidroxiapatita e, conseqüentemente, à superfície mineral óssea (Vasikaran, 2001). Com a descoberta de que os bisfosfonatos, além de inibirem a dissolução e crescimento de cristais de mineral, apresentam efeitos celulares sobre osteoclastos, seu uso em patologias caracterizadas por perda de densidade óssea se tornou amplamente difundido (Russell et al, 1999 (Russell, 2006).…”
Section: Bisfosfonatosunclassified
“…Após infusão endovenosa, é rapidamente eliminado do plasma e 40% são excretados pela urina, não sendo metabolizado no organismo. Como os demais bisfosfonatos, liga-se rapidamente à hidroxiapatita do osso, e sua meia-vida de eliminação estimada é de 12 anos (Vasikaran, 2001). O alendronato liga-se a superfícies ósseas durante o processo de reabsorção.…”
Section: Bisfosfonatosunclassified
See 1 more Smart Citation